Analisis Faktor Yang Memengaruhi Kedisiplinan Siswa Kelas IV - Setyowati Wahyuningsih; Dian Kusumawati; Mar’atul Faida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was conducted to examine the determinants contributing to the development of student discipline, encompassing both internal and external dimensions. A qualitative research design was applied, utilizing interviews with homeroom teachers, parents, and fourth-grade students as key informants. Data collection involved structured interview procedures supported by relevant documentation. The collected data were subsequently analyzed using descriptive techniques to identify the most influential factors shaping students’ disciplinary behavior. The findings reveal that the development of students’ disciplinary behavior emerges from the combined influence of internal and external factors. Internal aspects encompass learning motivation, levels of self-awareness, and students’ capacity to control and manage their own behavior. Meanwhile, external factors consist of teachers’ role modeling, the implementation of school rules, parental support, and the influence of the social environment. The findings reveal that external factors, particularly family support and consistency in the implementation of school rules, are the most dominant factors in shaping students’ discipline. Therefore, the development of students’ discipline requires cooperation among schools, families, and students to ensure that disciplined behavior can develop optimally and sustainably. Keywords: students’ discipline, internal factors, external factors, character education